HUBUNGAN USIA REPRODUKSI, JUMLAH ANAK, DAN RIWAYAT KONTRASEPSI PENGGUNAAN KONTRASEPSI SUNTIK DI PUSKESMAS PEDAMARAN TIMUR KECAMATAN PEDAMARAN TIMUR KABUPATEN OKI : Yulianita, Yulizar, Turiyani - Yulia Nita (JURNAL SMART ANKes, 2019)
Injectable contraceptives are effective and practical to use and are affordable and safe. The purpose of this study was to determine the relationship between reproductive age, number of children, and history of use of injection contraceptives at the Pedamaran Timur OKI Health Center, Pedamaran District, OKI Regency in 2019. This study used an analytical survey method with a cross sectional approach. The number of samples used was 306 samples. The data used in this research is secondary data. According to the results of the chi-square statistical test of reproductive age, the p-value was 0.001, the number of children was Pvalue 0.005, the history of contraceptive use was Pvalue 0.000, so it could be concluded that there was a significant relationship between childbearing age, the number of children and history of contraceptive use with the use of injection contraceptives at the Puskesmas Pedamaran Timur District of East Pedamaran District of OKI Regency in 2019. It is hoped that this research can be a means of providing counseling and counseling about contraception.